Characterisation of clutter loss using fish-eye lens for the prediction of DTV coverage - Peh, Beng Yeow. (2008)
Clutter loss depends very much on the terrain condition. When a DTV receiver is placed in areas where there are denser and taller buildings, the signal suffers more clutter loss than when it is placed in an environment with lesser and shorter buildings. The question is how to relate the terrain density with the clutter loss? This report aims to discuss the characterisation of the clutter loss using fish-eye lens for the prediction of Digital Television (DTV) coverage. A fish-eye lens captures 360° of the surrounding and produces a circular photo. Hence, it can be used to describe the terrain density. This project looks into the relationship between these terrain densities and the calculated clutter loss.